Pengaruh Inovasi Produk dan Kualitas Produk Terhadap Keunggulan Bersaing Pada Rumah Makan Batak di Kecamatan Alam Barajo Kota Jambi - Nurlianna Manik; Sigit Indrawijaya; Novita Ekasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effect ofproduct innovation and product quality partially and simultaneously oncompetitive advantage at Batak Restaurant inAlam Barajo District, Jambi City. Thisresearch uses a descriptive quantitative approach. The sampling method uses the Structural Equation Model method and uses Maximum Likehood Estimation (MLE). The sample inthis study were consumers at Batak Restaurant in Alam Barajo District, Jambi City, totaling 98 respondents. The data collected using a questionnaire withan ordinal scale. The data analysis method in this study usedSPSS version 25.0 software. The results ofthe study prove that Product Innovation and Product Quality have a significant effect simultaneously on Competitive Advantage, Product Innovation has a significant effect partially on competitive advantage and Product Quality has a partial effect on Competitive Advantage at Batak Restaurant in Alam Barajo District, Jambi City. The product quality variable is the most dominant variable affecting competitive advantage in Batak Restaurant in Alam Barajo District, Jambi City.